2018
DOI: 10.3390/app8071124
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Methods for Modelling of Wave Propagation in Structures in Terms of Damage Detection—A Review

Abstract: Modern methods of detection and identification of structural damage direct the activities of scientific groups towards the improvement of diagnostic methods using for example the phenomenon of mechanical wave propagation. Damage detection methods that use mechanical wave propagation in structural components are extremely effective. Many different numerical approaches are used to model this phenomenon, but, due to their universal nature, spectral methods are the most commonly used, of which there are several ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 142 publications
0
24
0
Order By: Relevance
“…To date, a number of vibration-based system identification and damage detection methods have been developed, and review articles with different emphases can be also found [2][3][4]. In general, structural parameters identification can be performed in three different paradigms: (i) time domain (e.g., [5][6][7][8][9][10]), (ii) frequency domain (e.g., [11][12][13][14]), and (iii) time-frequency domain (e.g., [15][16][17]).…”
Section: Literature Surveymentioning
confidence: 99%
“…To date, a number of vibration-based system identification and damage detection methods have been developed, and review articles with different emphases can be also found [2][3][4]. In general, structural parameters identification can be performed in three different paradigms: (i) time domain (e.g., [5][6][7][8][9][10]), (ii) frequency domain (e.g., [11][12][13][14]), and (iii) time-frequency domain (e.g., [15][16][17]).…”
Section: Literature Surveymentioning
confidence: 99%
“…Resuming, each nonlinear wave equation can be linearized by a non-local symmetry analysis (for more details, see Bluman-Cheviakov [4]). For further discussion about the potential benefit of this procedure, we refer to the papers by Taylor-Kidder-Teukolsky [5] and Palacz [6] (spectral methods for propagation phenomena).…”
Section: Introductionmentioning
confidence: 99%
“…For commonly used homogeneous and heterogeneous materials, dispersion relations have been documented in various handbooks and textbooks [7,8]. Numerical methods, such as time and frequency domain spectral element method [9][10][11][12], the semi-analytical finite element method [13,14], the wave finite element method [15,16], and transfer function and transfer matrix methods [17,18] have also been developed to describe wave propagation along uniform and periodically varying waveguides. For realistic wave propagation characteristics to be obtained, accurate description of material and geometric characteristics of the waveguide is required [19].…”
Section: Introductionmentioning
confidence: 99%